2016
DOI: 10.1590/s1677-5538.ibju.2015.0644
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparative study of rigid and flexible ureteroscopy for treatment of proximal ureteral stones

Abstract: Background:We analyzed the outcome and complications of rigid (R-URS) and flexible (F-URS) ureteroscopic lithotripsy for treatment of proximal ureteric stone (PUS).Subjects and methods:Retrospective data of 135 patients (93 males and 42 females) submitted to R-URS and F-URS for treatment of PUS in the period between July 2013 and January 2015 were investigated. (R-URS, group 1) was performed in 72 patients while 63 patients underwent (F-URS, group 2).We compared the 2 groups for success, stone characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
1
30
2
2
Order By: Relevance
“…But there may be other set of patients who might prefer to have their stone removed and the pain alleviated at the earliest possible time, thus avoiding multiple treatment sessions that might be required in case of SWL as treatment modality. [18,19] It was mentioned in a study that compared with SWL, ureteroscopic removal of ureteral stones achieved a greater stone-free status, but with a higher complication rate and longer hospital stay. [19] Lee et al [20] reported lack of any significant differences regarding patients' satisfaction for either intervention (URS or SWL).…”
Section: Discussionmentioning
confidence: 99%
“…But there may be other set of patients who might prefer to have their stone removed and the pain alleviated at the earliest possible time, thus avoiding multiple treatment sessions that might be required in case of SWL as treatment modality. [18,19] It was mentioned in a study that compared with SWL, ureteroscopic removal of ureteral stones achieved a greater stone-free status, but with a higher complication rate and longer hospital stay. [19] Lee et al [20] reported lack of any significant differences regarding patients' satisfaction for either intervention (URS or SWL).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to change the anesthesia type. There are numerous studies comparing the anesthesia types performed before sURS; however, most studies compare local anesthesia with GA or SA [ 9 13 ]. Frequently, carefully selected patients, such as those with distal ureteral stones and female patients were included in these studies, and thinner caliber ureteroscopes are used during the surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…AUA guidelines recommended that a FURS should be available when performing URS for proximal ureteric calculi [3]. Galal et al and Karadag et al compared both techniques for treatment of proximal ureteric calculi and reported that FURS offered significantly better stone free rate ( P = 0.005) but rigid URS had significantly shorter operative time (P = 0.005) and both had comparable complication rates [9, 10].…”
Section: Discussionmentioning
confidence: 99%